2018
DOI: 10.1123/jsr.2016-0099
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low-Intensity Therapeutic Ultrasound on Measurable Outcomes: A Critically Appraised Topic

Abstract: with the device secured to them, eliminating the portability constraint of traditional US units.Depending on the parameters chosen (refer to Table 2), the unit may provide treatment for up to 5 to 6 consecutive hours without needing to charge the unit battery. 3 Early studies suggest that this portable unit can deliver lower-intensity acoustic energy over a prolonged period of time (hours), as well as medium-intensity treatments over a shorter period of time (minutes), achieving the same temperature increase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…[24][25][26] The inconsistency of ultrasound treatment effectiveness cited in the literature and metanalysis can be attributed to a lack of optimization of ultrasound duty cycle, frequency, intensity, and power as well as patient compliance. [27][28][29] Over the last decade, research suggests daily increased energy deposition via low-intensity ultrasound can improve patients' quality of life. Low-intensity continuous ultrasound (LICUS) devices enable patients to self-apply non-invasive therapeutic ultrasound for up to four hours per day, increasing total energy deposition to almost 20,000 Joules compared to an ON/OFF 10 to 20-minute therapist applied ultrasound treatment, which typically involves 700 to 2,000 Joules of energy deposition once a week.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] The inconsistency of ultrasound treatment effectiveness cited in the literature and metanalysis can be attributed to a lack of optimization of ultrasound duty cycle, frequency, intensity, and power as well as patient compliance. [27][28][29] Over the last decade, research suggests daily increased energy deposition via low-intensity ultrasound can improve patients' quality of life. Low-intensity continuous ultrasound (LICUS) devices enable patients to self-apply non-invasive therapeutic ultrasound for up to four hours per day, increasing total energy deposition to almost 20,000 Joules compared to an ON/OFF 10 to 20-minute therapist applied ultrasound treatment, which typically involves 700 to 2,000 Joules of energy deposition once a week.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature reviews on LICUS have found the treatment is effective in decreasing pain and improving function in musculoskeletal injuries. 29 Additionally, ultrasound can have mechanical and biologically driven effects such as myoregeneration, 32 improve biomechanics, 31 anti-inflammatory, 39 and thermal effects. 33,34 The objective of this study was to determine the effectiveness of daily 4-hour LICUS at alleviating upper trapezius active myofascial pain and muscle tenderness over a 4-week treatment period.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical effect can regulate the cell membrane, increase protein synthesis, increase cell migration, promote vascular regeneration, and adjust the inflammatory response. Thermal responses include increased cell metabolism, improved local blood circulation, reduced pain, and alleviated muscle spasms . Esenyel et al used planar pulsed ultrasound for the treatment of 102 patients with neck and shoulder muscle pain, of whom 22.9% had significant pain alleviation after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation was beyond the scope of this research but could be considered in a future analysis paying close attention to time, duration, dose delivered and regularity of ultrasound treatment. The literature search strategy we employed found 13 relevant articles specific to SAM that are more than other past reviews on Sustained Acoustic Medicine ever, it is possible that some relevant studies were missed that were not available in English language or those in the grey literature which are emerging on this new therapeutic treatment [ 79 , 92 , 93 ]. Additionally, several of the outcome variables used in the studies differed in both measure, physical location on the body, condition being treated and control group which limited the scope of meta-analysis.…”
Section: Limitationsmentioning
confidence: 99%